Nuevas citas para la flora vallisoletana. - Lázaro Bello, Jesús Antonio (Acta Botanica Malacitana, 2002)
New floristic records for Valladolid province. Palabras clave. Corología. Flora Vascular. España. Valladolid. Renedo de Esgueva. Key words. Chorology. Vascular Flora. Spain. Valladolid. Renedo de Esgueva.